2017
DOI: 10.1242/dmm.028571
|View full text |Cite
|
Sign up to set email alerts
|

MMP-14 overexpression correlates with the neurodegenerative process in familial amyloidotic polyneuropathy

Abstract: Levels of matrix metalloproteases (MMPs) can be differentially regulated in response to injury or neurological diseases. For instance, it is known that selective and short-term inhibition of MMP-14, a membrane-type 1 MMP, accelerates axon regeneration. Because axon growth and regeneration is impaired in familial amyloidotic polyneuropathy (FAP), a neurodegenerative disorder characterized by misfolding and deposition of mutant transthyretin (TTR) in the peripheral nervous system (PNS), we presently investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…TTR non-fibrillar aggregates induce a cytotoxic response that involves mitochondrial dysfunction, endoplasmic reticulum stress, and dysregulation of the Ca 2+ balance. Consequently, these cytotoxic responses may result in ROS accumulation and inflammation progression [ 17 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…TTR non-fibrillar aggregates induce a cytotoxic response that involves mitochondrial dysfunction, endoplasmic reticulum stress, and dysregulation of the Ca 2+ balance. Consequently, these cytotoxic responses may result in ROS accumulation and inflammation progression [ 17 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…[97][98][99][100] The finding of smarca5 as an upregulated gene in the lakritz indicates the importance to address functional implications of this chromatin remodeling gene for atoh7-related eye disorders. Furthermore, the "neural retina development" Gene Ontology category encompassed the reportedly stress response genes hsp70.1(HSPA1L) 69 and mmp14 101 as significantly downregulated and upregulated, respectively, by the lakritz mutation. The crystallin related, heat shock Hsp70 family proteins are emerging as important regulators of RGC survival and regeneration as well as retinal vascular remodeling factors.…”
Section: Discussionmentioning
confidence: 99%
“…To explore other possible genetic factors that may modulate AO, we used a family centered approach and focused on candidate genes, C1QA and C1QC, which can affect functional pathways in the course of the disease. It is well recognized that inflammatory infiltrates are rarely seen in nerve biopsies, 26 but several authors found evidence of activation of inflammatory markers in the tissues of patients 27 and animal models 28,29 and even in the peripheral blood. 30 However, the primary or secondary role of these markers remains a matter of controversy.…”
Section: Discussionmentioning
confidence: 99%